Sex differences in hepatic and intestinal contributions to nevirapine biotransformation in rats. (25th May 2015) - Pinheiro, P.F.; Marinho, A.T.; Antunes, A.M.M.; Marques, M.M.; Pereira, S.A.; Miranda, J.P.
Highlights: There is a relevant extra-hepatic contribution to nevirapine (NVP) biotransformation. Inter-sex differences contribute to the variability in biotransformation of NVP. The major hepatic Phase I metabolite is 12-OH-NVP in males and 2-OH-NVP in females. 3- and 12-OH-NVP were found only in male intestinal perfusion solutions. 2-OH-NVP levels were higher in females, both in extraluminal and intraluminal media. Abstract: The understanding of the intestine contribution to drug biotransformation improved significantly in recent years. However, the sources of inter-individual variability in intestinal drug biotransformation, namely sex-differences, are still elusive. Nevirapine (NVP) is an orally taken anti-HIV drug associated with severe idiosyncratic reactions elicited by toxic metabolites, with women at increased risk. As such, NVP is a good model to assess sex-dimorphic metabolism. The aim of this study was to perform a comparative profiling of NVP biotransformation in rat intestine and liver and evaluate whether or not it is organ- and sex-dependent. Therefore, nevirapine-containing solutions were perfused through the intestine, in a specially designed chamber, or incubated with liver slices, from male and female Wistar rats. The levels of NVP and its Phase I metabolites were quantified by HPLC-UV. Liver incubation experiments yielded the metabolites 2-, 3-, 8-, and 12-OH-NVP, being 12-OH-NVP and 2-OH-NVP the major metabolites in males and females, respectively. Inter-sex differences in the metabolic profile were also detected in the intestine perfusion experiments. Herein, the metabolites 3- and 12-OH-NVP were only found in male rats, whereas 2-OH-NVP levels were higher in females, both in extraluminal ( p  < 0.01) and intraluminal media. The metabolite 8-OH-NVP was not detected in the intraluminal media from either males or females. In this study, important inter-sex differences were detected in both organs, providing further clues to the sex-dimorphic profile of NVP toxicity. Moreover, an extra-hepatic contribution to NVP biotransformation was observed, strengthening the relevance of the intestinal contribution in the biotransformation of orally taken-drugs.